Design and practical implementation of verify‐your‐vote protocol. (29th June 2020) - Chaieb, Marwa; Yousfi, Souheib; Lafourcade, Pascal; Robbana, Riadh
Summary: One of the most critical properties that must be ensured to have a secure electronic voting is verifiability. Political parties, observers, and especially voters want to be able to verify that all eligible votes are cast as intended and counted as cast without compromising votes secrecy or voters privacy. Over the past few decades, an important number of e‐voting protocols attempt to deal with this issue by using cryptographic techniques and/or a public bulletin board. Recently, some blockchain‐based e‐voting systems have been proposed, but were not found practical in the real world, because they do not support situations with large numbers of candidates and voters. In this article, we design and implement a verifiable blockchain‐based online voting protocol, called verify‐your‐vote . Our protocol ensures several security properties thanks to some cryptographic primitives and blockchain technology. We also evaluate its performance in terms of time, cost, and the number of voters and candidates that can be supported.